Does Soil Nutrient Heterogeneity Improve the Growth Performance and Intraspecific Competition of the Invasive Plant Myriophyllum aquaticum? - Shen, Nan; Yu, Hongwei; Yu, Siqi; Yu, Dan; Liu, Chunhua (Frontiers in Plant Science, 2019)
Spatial heterogeneity in soil nutrient availability is considered to play an important role in promoting plant invasion success and can affect interspecific competition. Although some clonal plants have been demonstrated to be correlated with resource heterogeneity in terrestrial systems, little is known about how soil nutrient heterogeneity affects the growth of invasive aquatic plants or their population structure. A greenhouse experiment was therefore conducted to study the response of the invasive aquatic plant Myriophyllum aquaticum to the spatial heterogeneity of soil nutrients under three plant densities (one, four, or twelve plants per container) with a constant amount of soil nutrients per container. The results showed that soil nutrient heterogeneity significantly increased the number of shoots in the single-plant density treatment. However, heterogeneous soil nutrient treatment significantly increased the number of shoots at the expense of total biomass and aboveground biomass in the twelve-plant density treatment. The heterogeneous soil nutrient treatment had few effects on other growth traits and intraspecific competition under different plant density treatments. These results indicate that spatial heterogeneity in soil nutrient availability may facilitate the spread of M. aquaticum.